STRATEGIC HUMAN RESOURCE MANAGEMENT - Greer Charles R (Prentice Hall, 2001)
HUMAN RESOURCE INVESTMENT CONSIDERATIONS INVESTMENTS IN TRAINING AND DEVELOPMENT INVESTMENT PRACTICES FOR IMROVED RETENTION INVESTMENTS IN JOB-SECURE WORKFORCES
HUMAN RESOURCE INVESTMENT CONSIDERATIONS INVESTMENTS IN TRAINING AND DEVELOPMENT INVESTMENT PRACTICES FOR IMROVED RETENTION INVESTMENTS IN JOB-SECURE WORKFORCES